Neural Tracking of Sound Rhythms Correlates With Diagnosis, Severity, and Prognosis of Disorders of Consciousness - Xu, Chuan; Zou, Jiajie; He, Fangping; Wen, Xinrui; Li, Jingqi; Gao, Jian; Ding, Nai; Luo, Benyan (Frontiers in Neuroscience, 2021)
Effective diagnosis and prognosis of patients with disorders of consciousness (DOC) provides a basis for family counselling, decision-making, and the design of rehabilitation programs. However, effective and objective bedside evaluation is a challenging problem. In this study, we explored EEG response tracking sound rhythms as potential neural markers for DOC evaluation. We analyzed the responses to natural speech and tones modulated at 2Hz and 41 Hz. At the population level, patients with positive outcomes (DOC-P) showed higher cortical synchronization to modulated tones at 41Hz compared with patients with negative outcomes (DOC-N). At individual level, phase coherence to modulated tones at 41-Hz was significantly correlated with Coma Recovery Scale-Revised (CRS-R) and Glasgow Outcome Scale-Extended (GOS-E) scores. Furthermore, SVM classifiers, trained using phase coherences in higher frequency bands or combination of the low frequency aSSR and speech tracking responses, performed very well in diagnosis and prognosis of DOC. These findings show that EEG responses to auditory rhythms is a potential tool for diagnosis, severity, and prognosis of DOC.